Transcriptional insights into gastrointestinal adaptations in pigs to high altitude - Ran, Bo; Tang, Jie; Wang, Yan; Tao, Xuan; Yang, Yuekui; Yang, Xuemei; Gong, Jianjun; He, Zhiping; Gu, Yiren; Liu, Pengliang; Liang, Yan (Frontiers in Veterinary Science, 2025)
Characterizing the transcriptomic profiles of gastrointestinal tract tissues in high-altitude pigs is crucial for understanding the molecular mechanisms underlying their metabolic adaptation to high-altitude environments. Here, we generated RNA-seq data from five gastrointestinal tract tissues (i.e., stomach, jejunum, cecum, colon, rectum) and the triceps brachii muscle of six 300-day-old castrated male Tibetan pigs (inhabiting high-altitude regions) and six Black pigs (inhabiting low-altitude regions). Pigs were group-housed and fasted for 24 h before sampling. We identified transcriptional differences between these two pig populations, revealing that genes upregulated in the gastrointestinal tract tissues and triceps brachii muscle of Tibetan pigs, compared to Black pigs, are primarily associated with immune response and metabolic processes, including lipid metabolism. Consistently, a comparative analysis demonstrated that the fatty acid content was higher in the triceps brachii muscles of Tibetan pigs than in those of Black pigs. Additionally, we identified 18 genes, including HDC, SETD9, HUS1, and RPSA, whose expression in gastrointestinal tract tissues was significantly correlated with the metabolite abundance (amino acid and fatty acid, etc.) in the triceps brachii muscles. This study may contribute to the understanding of high-altitude adaptation mechanisms in Tibetan pigs and provides valuable insights for further genetic improvement of pig breeds.